2020
DOI: 10.12955/pmp.v1.92
|View full text |Cite
|
Sign up to set email alerts
|

Methods to Determine Complex Degrees of Mutual Anisotropy for the Differentiation of Hemorrhages in the Human Brain Substance Resulting From Traumatic and Non-Traumatic Genesis

Abstract: An issue that is often debated in forensic traumatology is the differential diagnosis of hemorrhages into the human brain substance (HBS) of traumatic and non-traumatic genesis. Objectives. This study aims to identify new criteria for objective forensic differentiation of hemorrhages of traumatic origin, cerebral infarction of ischemic and hemorrhagic genesis by using the method of complex degree of mutual anisotropy. For this study native sections of HBS from 125 corpses were used in the case of: death … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…At the next step of the research, we analyzed the strength of the azimuthal-invariant MM polarimetry method to distinguish the cause of death between research groups. An increase in the value of sensitivity (Se,%), specificity (Sp,%), and balanced accuracy (Ac,%) in 14% -19% compared to the data of previous MM-mapping researches of TMS (Garazdiuk et al, 2020).…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…At the next step of the research, we analyzed the strength of the azimuthal-invariant MM polarimetry method to distinguish the cause of death between research groups. An increase in the value of sensitivity (Se,%), specificity (Sp,%), and balanced accuracy (Ac,%) in 14% -19% compared to the data of previous MM-mapping researches of TMS (Garazdiuk et al, 2020).…”
Section: Resultsmentioning
confidence: 69%
“…(Sivokorovskaya et al, 2020) demonstrated the role of polarization-phase diagnostics of the volume of blood loss. Our previous studies demonstrated the efficacy of thin-layer polarization tomography to differentiate the origin of hemorrhage into the brain (Garazdiuk et al, 2020). For a forensic expert-practitioner, the main thing is objectivity, accuracy, and speed of obtaining the result, which could fully satisfy the 1 Bukovinian State Medical University, Department of Forensic Medicine and Medical Law, Chernivtsi, Ukraine, m.garazdiuk@gmail.com, ORCID 0000-0003-1536-4440 2 Bukovinian State Medical University, Department of Forensic Medicine and Medical Law, Chernivtsi, Ukraine, sudmed@bsmu.edu.ua, ORCID 0000-0002-6955-7507 3 Bukovinian State Medical University, Department of anesthesiology and reanimatology, Chernivtsi, Ukraine, olena.nechytailo@bsmu.edu.ua, ORCID 0000-0003-3932-4902 4 Bukovinian State Medical University, Internal Medicine and Infectious Diseases Department, Chernivtsi, Ukraine, olexandr.harazdiuk@gmail.com, ORCID 0000-0002-0430-7558 methods of laser polarimetry in the case of differential diagnosis of hemorrhages of traumatic and nontraumatic origin in the human brain (Hao & Wang, 2017).…”
Section: Introductionmentioning
confidence: 99%